Meta Analisis: Pendekatan Realistics Mathematics Education (RME): Hasil Riset - Zulfah Zulfah; Gita Nirmala; M. Rico Fahrul; Nurul Rahma; Risa Meilani Haryanto; Yeni Agustina; Yusi Ahadna; Agus Dermawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
This research was conducted to determine the Realistics Mathematics Education (RME) approach can be used as a solution in learning mathematics. The research method used in the form of experimental research in the form of a post test and there is a control class and an experimental class. This research method is a meta-analysis with a sample of 4 articles in national journals accredited by Sinta 3-6 with the research subject being junior high school education. The meta-analysis research shows that the effect of the Realistics Mathematics Education (RME) learning approach is effective on math skills. From the subject matter of the 4 articles analyzed, RME has more influence on the material of a two-variable linear equation system, geometry, algebra than other materials. The results showed that there was a better positive response and active learning of students using the Realistic Mathematical Education (RME) approach than those using ordinary learning, and had positive impacts such as more interactive learning, more meaningful learning and being able to understand concepts.